ANALISIS SISTEM AKUNTANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN BADAN USAHA MILIK DESA (BUM DESA) (Studi Kasus : BUM Desa di Kec. Galesong Utara Kabupaten Takalar) - Haeruddin Haeruddin; Lina Mariana (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2021)
Village-owned enterprises (BUM Desa) in Takalar District, in terms of practice, the accounting system is still very simple and has not been able to present proper financial reporting so that financial accountability is still considered very weak. The results of the research are 1) Bumdes financial management uses a simple bookkeeping system and does not reflect systematic and accurate financial reporting based on permitted Financial Accounting Standards, 2) The presentation of financial statements is not correct which then has an impact on the performance and financial position of the entity. 3) the financial information of Bumdes is not in accordance with the principles of accountability, including (a) there is a commitment from the leadership and all staff to manage an organization that has an accountable value, (b) is a system that ensures consistent use of resources based on laws and regulations that applies, (c) shows the level of achievement of the goals and objectives that have been set, (d) oriented to the vision, mission, results, and benefits obtained by the organization, (e) upholds the values ​​of honesty, transparency, objectivity and innovation.